Advances in Animal Anatomy - Fernández, Matilde Lombardero; Yllera Fernández, María del Mar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue covers current and relevant information about the applied anatomy of domestic animals, new companion animals and wild animals. It includes recent research and review articles on diverse topics based on the use of different diagnostic imaging techniques and more classic anatomical methods, providing a deeper insight into the healthy anatomy of diverse structures, which is crucial in high-quality medicine.